THE IMPACT OF GENDER STEREOTYPES ON WOMEN’S PRODUCTIVITY IN THE CIVIL SERVICE: EVIDENCE FROM KEBBI STATE - Omoruan, Augustine Idowu; Abah, Stella Ozioma; Phillips, Oluwaseun Foluso; Bamidele, Akinfemi Philip; Oduola, Taofiq Omotayo (African Journal of Social and Behavioural Sciences, 2025)
Gender stereotypes pose a substantial challenge in professional settings, particularly within public service institutions where traditional norms and cultural expectations profoundly influence workplace dynamics. In Nigeria’s civil service, despite the presence of policies promoting gender equality, women in Kebbi State often face biases deeply rooted in societal perceptions. This study examines the impact of gender stereotypes on women’s productivity in the Kebbi State Civil Service. To conduct this research, a survey was administered to 198 employees randomly selected from various ministries. A semi-structured questionnaire was employed to collect data, which was subsequently analysed using SPSS version 28. Three research questions were formulated alongside corresponding hypotheses to test key variables in the study. Descriptive statistics, including mean and standard deviation, were utilised to address the research questions, while Spearman’s rank correlation coefficient was applied to test the hypotheses at a 0.05 significance level. The results indicated a significant positive relationship between gender stereotypes and the allocation of tasks and opportunities for women in the civil service. Furthermore, the perception of women as less competent in decision-making roles was found to significantly hinder their professional growth. Based on these findings, the paper recommends a thorough review of employment policies and the implementation of strategies and programs, including mentorship initiatives, to foster organisational cultural change and eliminate obstacles to women’s productivity.